Coordinating Intergenerational Redistribution and the Repayment of Public Debt - Christoph March; Robert K. von Weizsäcker (Center for Economic Studies and ifo Institute (CESifo), 2016)
Is there a link between public debt and wealth inequality? Could government bondholders use intra-generational redistribution strategically to make the repayment of debt politically viable? Using a two-generations game-theoretic model, we identify coordination and divide-and-conquer as key factors. By coordinating their bond investments, the old generation may secure a majority favoring debt repayment. As a consequence, coordination mediates the impact of wealth inequality on public debt. Furthermore, ease of coordination offers another compelling reason why declining population growth fosters the accumulation of public debt. We test our model in a laboratory experiment and confirm the central predictions.
Keywords: H23; H63; D72; C92; 330; government debt; intergenerational conflict; voting; experimental economics